Application Tabarru’ and Tijarah Contract on Sharia Insurance - Mohammad Ghozali; Amatullah Nur Afifah (AL- IKTISAB Journal of Islamic Economic Law, 2020)
In insurance has a contract that has been determined by sharia and has been written in the DSN-MUI namely there are tabarru’ and tijarah. See the contract offered by sharia insurance then this research aims to analyze how the application tabarru’ and tijarah authorizes in sharia insurance. The method used in this study is qualitative. The result of this study is wherein the tabarru’ have a purpose please help between insurance participants and tijarah authorizes have a commercial purpose, where the participant as a mall and company shohibul as a fundraiser. In this case, the tijarah authorizes can be turned into a tabarru’ contract when the party is willing to release its right to be transferred to tabarru’ fund. But instead, the tabarru’ can not turn into a tijarah.